Public procurement quality assessment of a region: regression analysis - Belokrylova, Olga S; Belokrylov, Kirill A; Tsygankov, Sergey S; Syropyatov, Vadim A; Streltsova, Elena D (International journal of sociology and social policy, 2021)
PurposeThe paper aims to present the results of a study aimed at constructing economic and mathematical models used in decision-making in the management of budget procurement of a region, contributing to the efficient use of budget funds. One of the key problems in this area is the assessment of the quality of procurementDesign/methodology/approachOne of the key problems in this area is the assessment of the quality of procurement, the solution of which requires the application of economic and mathematical methods, models, tools and algorithms built into information systems for supporting decision-making. The introduction of these systems brings to a qualitatively new level the system of relations between subjects of budget procurement. The paper analyzes modern publications on the implementation of public procurement and related issues of efficiency (savings) of budgetary funds.FindingsThe indicators on the basis of which the evaluation of the quality of regional procurement is determined are proposed. The architecture of the information system for decision support in the evaluation of procurement quality has been developed. The system has the property of adapting to changes in the state of the environment through the constant accumulation of statistical data characterizing the procurement and adjustment of the parameters of the mathematical model in accordance with them. A mathematical model is built into the control loop that allows ranking the indicators of budget purchases by the degree of their influence on the effective attribute. The role of a functional feature is the quality of budget procurement. The mathematical model is based on the application of the mathematical apparatus of correlation and regression analysis. The impact of each of the factor attributes on the functional attribute has been assessed.Originality/valueThe mathematical model is based on the application of the mathematical apparatus of correlation and regression analysis. The impact of each of the factor attributes on the functional attribute has been assessed. Real statistics are given that characterize budget procurements carried out in retrospect. The coefficients of the linear regression model are determined based on the use of the STATISTICA application software package. The proposed decision support information system with a regression model built into it allows one to make scientifically and quantitatively sound decisions when assessing the quality of budget purchases of a region.